Effects of short-term l-arginine supplementation on lipid profile and inflammatory proteins after acute resistance exercise in overweight men - Nascimento, M. A.; Higa, E. M.S.; de Mello, M. T.; Tufik, S.; Oyama, L. M.; Santos, R. V.; Amaya Farfan, J.; Risso, E. M.; De Souza, C. T.; Pimentel, G. D.; Lira, F. S. [UNESP] (Elsevier, 2014)
Background & aim: Dyslipidemia is involved with in development of cardiovascular diseases and obesity, exercise is recommended as a successful intervention. Dietary l-arginine (l-arg) supplementation may improve in lipid metabolism. However, these combined strategies on lipid profile were not tested yet. This study examines the effects of short term of l-arg supplementation and acute resistance exercise (AREX) on the blood lipid profile and inflammatory proteins in overweight men. Methods: Seven overweight men, 46±5yrs, body weight 93.1±12.0Kg and BMI 31.7±3kg/m2, participated in a randomized, double-blind and crossover study, distributed into exercise groups, based on the supplementation (6g/day of placebo or Arginine for 7 days). Supplementation periods were separated by 7-days of wash-out. The AREX was comprised of eight exercises, with an exercise intensity of 60% 1RM. The glucose, lipid profile (NEFA, triglycerides, HDL cholesterol, LDL cholesterol and total cholesterol) and inflammatory proteins [plasminogen activator inhibitor-1 (PAI-1) and adiponectin] were determined at rest, immediately, after exercise and 1h after exercise sessions. Results: Triglycerides, total cholesterol, and adiponectin levels not showed time-dependent changes under the different conditions. LDL cholesterol and NEFA levels decreased after 1h recovery periods when compared to rest periods only in l-arg supplementation group (P<0.05). PAI-1 was reduced and HDL cholesterol exhibits increases immediately after AREX and 1h recovery periods when compared with rest periods in both groups (P<0.05). Conclusion: These results indicate that l-arg supplementation can potentiate the effects of exercise inducing changes in the LDL cholesterol and NEFA levels. © 2014 European Society for Clinical Nutrition and Metabolism.
Keywords: Arginine supplementation; Dyslipidemia; Overweight; Plasminogen activator inhibitor-1; Resistance exercise